The role of lubricant feed temperature on the performance of twin groove journal bearings : an experimental study - Brito, F. P. (2011)
An experimental assessment of the influence of lubricant feed temperature (Tf) on the behaviour of twin groove hydrodynamic journal bearings has been undertaken. Several loads, shaft speeds and bearing geometries were tested under constant lubricant feed pressure (pf), while Tf took four different values between 29ºC and 58ºC. It was found that the increase of Tf has an effect in bearing performance which is analogous in many ways to the effect of the increase in eccentricity: increase in lubricant flow rate (especially in the low eccentricity range), in outlet temperature (Tout) and in maximum bush temperature (Tmax). Nevertheless, the latter increase was lower than the corresponding increase in Tf. Also, in the high eccentricity range the increase in flow rate due to the increase of Tf could be deceiving in the sense that the additional flow was supplied mainly to the inactive region of the bearing (the unloaded land of the bearing).